The Gene FvTST1 From Strawberry Modulates Endogenous Sugars Enhancing Plant Growth and Fruit Ripening - Rashid, Arif; Ruan, Haixiang; Wang, Yunsheng (Frontiers in Plant Science, 2022)
In different plant organelles, distinct types of sugars are accumulated, which directly influences plant growth. Sugar transporters are key modulators for inter-and intracellular sugar transport and distribution. There are four tonoplast sugar transporters (TSTs) in strawberry, in which the spatial expression of FvTST1 is closely associated with fruit ripening. Analyses of subcellular localization revealed that FvTST1 is located in tonoplast, and its function as sugar transporter has been proved through yeast expression system. Transient expression and stable transformation in strawberry and tomato both indicate that this gene is associated with sugar abundance and fruit ripening. In addition, FvTST1 transformed tomato plants grow fast, early flowering, and bears fruit significantly earlier than control. To reveal the mechanism of fast growth and development, transgenic tomato seedlings were characterized further. The transgenic tomato seedlings exhibited higher sucrose and auxin content, enhanced seed germination, hypocotyl elongation, root growth, and photosynthetic rate as compared to the non-transgenic control. Moreover, a transcriptomic study revealed that the auxin signaling pathway was the most significantly up-regulated Gene-ontology (GO) term among 1888 differentially expressed genes (DEGs). A total of 45 auxin activated pathway genes were up regulated. The expression of transcriptional factor genes phytochrome-interacting factor PIF1,-3, and-4, and their potential target genes, such as brassinosteroid signaling positive regulator1 (BZR1), gibberellin 2-beta-dioxygenase2 (GA2ox2), tryptophan aminotransferase of Arabidopsis1 (TAA1), and indole-3-acetic acid inducible29 (IAA29), were induced in transgenic seedlings. Thus, we concluded that enhanced seedling growth is concomitant with the enhancement of endogenous sucrose via FvTST1, and the endogenous sucrose-induced auxin signaling pathway, which highlights the biological significance of this gene for future breeding purposes.